ANTHRAX IN THE ASIAN PART OF THE RUSSIAN FEDERATION. COMMUNICATION 1. HISTORICAL REMARKS ON THE SPREAD OF THE DISEASE IN SIBERIA AND FAR EAST - Z. F. Dugarzhapova; M. V. Chesnokova; E. G. Gol’dapel’; S. A. Kosilko; Т. I. Innokent’eva; S. V. Balakhonov (Проблемы особо опасных инфекций, 2017)
The paper presents the data describing historical aspects of anthrax dissemination in Siberia and Far East. This disease has engrained here and spread throughout the entire Asian part of Russia. The majority of the soil anthrax foci are concentrated in the southern entities of the country. Siberia and Far East regions are characterized by low anthrax incidence rates among the population. This is due to the peculiarities of stock-animal farming and low population density. Historically, the establishment of a significant number of stationary hazardous as regards anthrax areas and soil foci is occasioned by the lack of proper veterinary surveillance and support of preventive activities aimed at the disposal of dead animals. Sporadic occurrence of epizootic complications on anthrax in the same areas indicates the persistence of soil anthrax foci.